Pemberdayaan Guru SDN 03 Kampung Olo, Nanggalo, Padang dalam Pembuatan Video Pembelajaran tentang Perilaku Hidup Sehat dan Bersih (PHBS) - Boby Febri Krisdianto; Arif Rohman Mansur; Ika Sari Wahyuni; Meza Silvana; Ria Febrina; Taufik Febriyanton; Annisa Rahma Yuni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
During the Covid-19 pandemic, elementary schools (SD) in Indonesia were required to take school lessons online. However, many teachers do not know how to teach effectively for their students. This condition causes many parents of elementary school students confused in children's learning assistance. Another condition is poor communication with the teachers. In addition, teachers also need to prepare their students for reopening schools through teaching about Healthy and Clean Living Behavior, named PHBS in Bahasa. This service aims to empower elementary school teachers; in this case the subject is the teacher at SDN 03 Kampung Olo so that they can make interactive and interesting health education learning videos. Trainers taught about the use of simple media for making instructional videos such as screen recording technology and video editing using smartphones and laptops for education such as Canva and Filmora. The trainer also provided learning videos, booklets, and helps to provide a learning studio in the form of a green screen and audio microphone. Then this workshop produced a learning video about Clean and Healthy Living Behaviors for students. The result of this activity was an increase in the knowledge and skills of teachers of SDN 03 Kampung Olo, Nanggalo, Padang in making interactive learning videos and clean living habits (PHBS) and it is hoped that it can increase the awareness of teachers, students and parents of students with PHBS.